2015
DOI: 10.1111/codi.12921
|View full text |Cite
|
Sign up to set email alerts
|

Extralevator abdominoperineal excision for low rectal cancer: a systematic review and meta‐analysis of the short‐term outcome

Abstract: The current evidence does not indicate a statistically significant superiority of ELAPE over conventional APE in terms of CRM positivity and intra-operative bowel perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 35 publications
(65 reference statements)
1
32
0
1
Order By: Relevance
“…initial enthusiasm for extralevator abdominoperineal resection has been tempered recently by studies suggesting equivalent local recurrence rates, long-term oncological outcomes, and lower morbidity with standard abdominoperineal resection when performed by dedicated colorectal surgeons. 38,39 akin to the current situation with abdominoperineal resection and the tailoring of resection extent to tumor stage (ie, standard abdominoperineal resection or extralevator abdominoperineal resection), tatme should perhaps be selectively used for low rectal tumors without t4 extension, because many studies excluded patients with this tumor subset. 29,30 a number of randomized controlled trials have been prospectively registered on trial databases and are actively enrolling.…”
Section: Survival and Functionalmentioning
confidence: 99%
“…initial enthusiasm for extralevator abdominoperineal resection has been tempered recently by studies suggesting equivalent local recurrence rates, long-term oncological outcomes, and lower morbidity with standard abdominoperineal resection when performed by dedicated colorectal surgeons. 38,39 akin to the current situation with abdominoperineal resection and the tailoring of resection extent to tumor stage (ie, standard abdominoperineal resection or extralevator abdominoperineal resection), tatme should perhaps be selectively used for low rectal tumors without t4 extension, because many studies excluded patients with this tumor subset. 29,30 a number of randomized controlled trials have been prospectively registered on trial databases and are actively enrolling.…”
Section: Survival and Functionalmentioning
confidence: 99%
“…In a recent retrospective study, Stelzner et al[3] showed that the 5-year recurrence rate was 5.9% in the ELAPE group vs 18.2% in the cAPR group ( P = 0.153). However, other units have not been able to reproduce such results[4], nor could they demonstrate a statistically significant superiority of ELAPE in terms of CRM positivity and bowel perforation. Furthermore, they reported comparable perineal complication rates for the two APR approaches.…”
Section: Introductionmentioning
confidence: 99%
“…We observed a higher incidence of perineal wound morbidity in the ELAPE arm. Although some earlier reports mention that delayed perineal wound healing is significantly higher after ELAPE than after an APE , a few others report comparable perineal wound morbidity . The uniform use of NCRT in our study would have further contributed to the delayed healing of the perineal wound.…”
Section: Discussionmentioning
confidence: 56%
“…None of the ELAPE specimens in the present study had an IOP; this contrasted with the CAPE specimens, in which an IOP of 30% was observed. Three meta‐analyses have shown that IOP rates are significantly reduced after an ELAPE , whereas another meta‐analysis showed a borderline decrease in the IOP rate after ELAPE . The randomized trial by Han et al .…”
Section: Discussionmentioning
confidence: 99%